Association of processes of primary care and hospitalisation for people with diabetes: A record linkage study. Issue 2 (May 2015) - Comino, Elizabeth Jean; Islam, MD Fakhrul; Tran, Duong Thuy; Jorm, Louisa; Flack, Jeff; Jalaludin, Bin; Haas, Marion; Harris, Mark Fort
Highlights: We explore the association between diabetes primary care processes and hospitalisation. Implementing recommended diabetes care is associated with reduced hospitalisation. Review of, and not just preparation of, management plans is required. Access to quality primary care provides alternatives to hospital presentation. Hospital avoidance programmes must support a strong primary care sector. Abstract: Aims: To explore the association of primary care and hospitalisation for people with diabetes. Methods: The study comprised 20, 433 diabetic participants in the Sax Institute's 45 and Up Study. Data on processes of care at recruitment (15 months) were extracted from the Department of Human Services Medicare database. Processes included continuity of primary care (47.1%), and claims for completion of an annual cycle of care (25.0%), GP management plan/team care arrangement (GPMP/TCA, 41.3%), review of GPMP/TCA (24.0%), and monitoring including HbA1c (62.7%). Hospitalisation (12 months) following recruitment was extracted from administrative data held by NSW Ministry of Health. Adjusted incidence rate ratios (aIRR) with 95% confidence interval were calculated. Results: A hospital admission was reported for 33.0% of participants. Continuity of care (aIRR: 0.92 (95%CI: 0.89–0.96)), or claims for an annual cycle of care (aIRR: 0.77 (0.74–0.80)) or HbA1c testing (aIRR: 0.92 (0.89–0.96) were associated with a reduced likelihood of hospitalisation. While claims for preparation of GPMP/TCA were not associated with hospitalisation, a claim for review of GPMP/TCA was associated with a reduced likelihood of hospitalisation (aIRR: 0.92 (95%CI: 0.89 0.96)). Conclusions: This study has implications for hospital avoidance programmes suggesting that strengthening primary care may be more important than care coordination for this group of patients.